RUSSIAN PHRASEOLOGY AS AN OBJECT OF RESEARCH AND TEACHING - Bogdanovich Gennady Aleksandrovich Kosimov Ulugbek Abdullaevich Karabayeva Aziza Sadykovna (Ethiopian International Journal of Multidisciplinary Research, 2023)
the article examines Russian phraseology as an object of research and teaching. The idea is expressed about the ambiguity of the term “phraselogy” itself and the need to create an academic-type phraseological dictionary.